2015
DOI: 10.1109/tps.2015.2445093
|View full text |Cite
|
Sign up to set email alerts
|

Physics of Spotless Mode of Current Transfer to Cathodes of Metal Vapor Arcs

Abstract: A fresh attempt is made to clarify the physics of the diffuse, or spotless, mode of current transfer that may occur on cathodes of vacuum arcs if the average cathode surface temperature is high enough, about 2000 K. It is shown that in the case of chromium cathode the usual mechanism of current transfer to arc cathodes cannot sustain current densities of the order of 10 5 -10 6 A · m −2 observed in the experiment, the reason being that the electrical power deposited into electron gas in the nearcathode space-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…[This happens when the average temperature of the cathode surface is high enough, typically around 2000 K (see [1] and the references therein). It is interesting to note that the physics of this regime, while supposedly being relatively simple, still has not been fully understood (see [2] and the references therein.)] On the other hand, in most cases, the current on the cathode of a vacuum arc is localized in bright, narrow regions, or cathode spots.…”
Section: Introductionmentioning
confidence: 99%
“…[This happens when the average temperature of the cathode surface is high enough, typically around 2000 K (see [1] and the references therein). It is interesting to note that the physics of this regime, while supposedly being relatively simple, still has not been fully understood (see [2] and the references therein.)] On the other hand, in most cases, the current on the cathode of a vacuum arc is localized in bright, narrow regions, or cathode spots.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed complete models for e.g. a vacuum arc with a chromium cathode [7] and also for a tungsten inert gas welding arc [20] have shown that a considerable part of energy required in the cathode layer is provided by the plasma bulk and transferred by electron energy flux.…”
Section: Discussion Of the Energy Balance Of The Edaccmentioning
confidence: 99%
“…[4] or [5] are not yet well established and investigated. One of the reasons is that the most prominent approaches for the consideration of the plasma-cathode interaction tend to predict cathode surface temperatures that are considerably higher than boiling temperature >3144 K [6][7][8]. However, in the actual process, neither boiling, nor the highly constricted cathode spots, which might justify such local overheating, can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many models developed for cathodic attachment, that have been very successful in their prediction of the conditions at the cathode in an arc discharge, these models usually refer to either vacuum arcs [7] or tungsten cathodes [8]. Both these conditions are not present in the case of GMAW.…”
Section: Introductionmentioning
confidence: 99%